ANTIMICROBIAL PROPERTIES OF ELECTRICALLY FORMED ELASTOMERIC POLYURETHANE-COPPER OXIDE NANOCOMPOSITES FOR MEDICAL AND DENTAL APPLICATIONS - (:unkn) unknown (ELSEVIER ACADEMIC PRESS INC, 2012)
With the rapidly advancing field of nanotechnology having an impact in several areas interfacing life and physical sciences, the potential applications of nano particles as antimicrobial agents have been realized and offer great opportunities in addressing several viral and bacterial outbreak issues. Polyurethanes (PUs) are a diverse class of polymeric materials which also have applications in several areas of biomedical science ranging from blood contact devices to implantable dental technologies. In this report, copper oxide (CuO) nanoparticles (mean size similar to 50 nm) are embedded into a PU matrix via two electrical fabrication processes. To elucidate the antimicrobial activity, a range of different loading compositions of CuO within the PU matrix (0%, 1%, 5%, and 10% w/w) are electrospun to form thin porous films (thickness <10 mu m). After washing, the films are tested for their antimicrobial properties against methicillin-resistant Staphylococcus aureus (MRSA). Significant reduction of populations was demonstrated with 10% w/w CuO over a 4-h period. This approach demonstrates the potential of generating tailored antimicrobial structures for a host of applications, such as designer filters, patterned coatings, breathable fabrics, adhesive films (as opposed to sutures), and mechanically supporting structures.
Keywords: BIOMEDICAL APPLICATIONS; NANOPARTICLES; COMPOSITES; POLYMERS; SILVER